Effectiveness Of Baby Gym In Stimulating Motor Skills Rough Infants Aged 6–9 Months In Siak Hulu District In 2025 - Qomariah, Siti; Sara Herlina; Wiwi Sartika (Jurnal Maternitas Kebidanan, 2025)
Infancy is a golden age and development period for babies. At the age of 6-9 months, the baby's gross motor skills begin by sitting without support then standing with support. Baby gym is a technique that stimulates growth, development, especially in gross motor skills for babies optimally. In Indonesia itself, 7.5% of babies experience developmental delays. Purpose This study aims to determine the effectiveness of baby gym in stimulating gross motor skills in babies aged 6-9 months. This research method uses a quasi experiment with a pre-test post-test one group research design. The sample in this study were babies aged 6-9 months, the sample size used in the study was 30 babies. Data collection was carried out by conducting observations and questionnaires that had been tested for validity and reliability. The results of the study stated that the effectiveness of baby gym in stimulating gross motor skills in babies aged 6-9 months was obtained with ap value of 0.000. So it can be concluded that there is effectiveness of baby gym in stimulating gross motor skills in babies aged 6-9 months.